Analysis Of Relationship Marketing, Customer Trust, Price Competition On Customer Satisfaction Of Indihome Users In Medan City - Anandya Wahyu Lestari; Ari Prabowo (International Forum of Researchers and Lecturers, 2024)
Customer satisfaction includes efforts to meet consumer needs. Consumer satisfaction is a situation demonstrated by consumers when they realize that their needs and desires are as expected and are being fulfilled well. This research aims to determine and analyze the influence of relationship marketing, customer trust, and price competition on consumer satisfaction of Indihome users in Medan City. With a sample size of 100 respondents. Data collection techniques were carried out using questionnaires. The analysis used is multiple linear regression analysis using the SPSS (Statistical Package for Social Sciences) 24.0 for Windows program tool. The results of the analysis show that relationship marketing has a positive and significant influence on consumer satisfaction. Customer trust has a positive and significant influence on consumer satisfaction, and price competition has a positive and significant influence on consumer satisfaction. Meanwhile, the results of the simultaneous analysis show that relationship marketing, customer trust, and price competition have a positive and significant effect on consumer satisfaction of Indihome users in Medan City.